Involvement of Traditional Villages in Combating the Covid 19 Pandemic in Bangli - I Gusti Bagus Suryawan; NM Jaya Senastri; I Wayan Arthanaya; A.A. Ayu Wulan Pramesti; Klaustra Adhi Permana (Warmadewa Press, 2022)
The purpose of this study was to analyze the justification for the involvement of Traditional Villages in the implementation of the prevention and control of the Covid 19 Pandemic in Yang Api Village and Peninjoan Village. The Bali Provincial Government synergizes activities to prevent the transmission of the Corona Virus (Covid-19) by involving Indigenous Villages in Bali. The implementation of policies such as PPKM in traditional villages cannot be carried out alone by the government but requires cooperation with various parties, including the community, health workers and security officers. In general, Babinkamtibmas are security officers in the village. However, in Bali, every traditional village has a pecalang as a traditional security officer based on traditional local wisdom. The local government through the Decree on the formation of the Customary Village-based Mutual Assistance Task Force has provided space for indigenous village communities to independently handle the Covid-19 pandemic faced by the Fire and Peninjoan Traditional Villages. With the provision of this space, the Covid-19 Gotong Royong Task Force can handle the ongoing pandemic on its own, starting from education, socialization, prevention and even handling. In addition, traditional villages also receive support from the Village Service so that they can coordinate with each other. The maintenance of conduciveness in the village is carried out well, with the synergy of traditional villages with official villages in handling Covid-19. The involvement of elements of the Traditional Village (pecalang) in a pandemic emergency situation is indeed possible and does not become a serious problem because what is put forward is the principle of benefit for humanity. Meanwhile, the success rate of involving traditional pecalang in Yang Api and Peninjoan Villages has worked well, although in August there was a surge in people infected with Covid 19, but it was more due to the many traditional events in the village, and not because of the negligence of the Covid task force in synergizing its main functions. The positive performance of the involvement of traditional villages in pandemic prevention needs to be continued in the future for activities that benefit the indigenous village community.